Transcription mapping of the 5q- syndrome critical region: cloning of two novel genes and sequencing, expression, and mapping of a further six novel cDNAs. - Boultwood, J; Fidler, C; Strickson, A; Watkins, F; Kostrzewa, M; Jaju, R; Müller, U; Wainscoat, J (2000)
The 5q- syndrome is a myelodysplastic syndrome with the 5q deletion ¿del(5q) as the sole karyotypic abnormality. We are using the expressed sequence tag (EST) resource as our primary approach to identifying novel candidate genes for the 5q- syndrome. Seventeen ESTs were identified from the Human Gene Map at the National Center for Biotechnology Information that had no significant homology to any known genes and were assigned between DNA markers D5S413 and D5S487, flanking the critical region of the 5q- syndrome at 5q31-q32. Eleven of the 17 cDNAs from which the ESTs were derived (65%) were shown to map to the critical region of the 5q- syndrome by gene dosage analysis and were then sublocalized by PCR screening to a YAC contig encompassing the critical region. Eight of the 11 cDNA clones, upon full sequencing, had no significant homology to any known genes. Each of the 8 cDNA clones was shown to be expressed in human bone marrow. The complete coding sequence was obtained for 2 of the novel genes, termed C5orf3 and C5orf4. The 2.6-kb transcript of C5orf3 encodes a putative 505-amino-acid protein and contains an ATP/GTP-binding site motif A (P loop), suggesting that this novel gene encodes an ATP- or a GTP-binding protein. The novel gene C5orf4 has a transcript of 3.1 kb, encoding a putative 144-amino-acid protein. We describe the cloning of 2 novel human genes and the sequencing, expression patterns, and mapping to the critical region of the 5q- syndrome of a further 6 novel cDNA clones. Genomic localization and expression patterns would suggest that the 8 novel cDNAs described in this report represent potential candidate genes for the 5q- syndrome.